How is gentrification lived: a psycho-social study of the experience of gentrification in Lisbon - Ribeiro, Robyn Lea (2021)
Gentrification and Touristification are two concepts that over the past years have been focused on in various European countries, due to their implications for communities that live in certain neighbourhoods. The study of these concepts is crucial to understand the changes that have occurred in neighbourhoods at an economic, social, and psychological level. The present dissertation aims to understand the experience of Gentrification and Touristification of those who continue living in the neighbourhood at the level of place attachment, social bonds and emotions triggered. We executed a qualitative study with a sample of seven Santos-o-Velho neighbourhood inhabitants (in Lisbon) diverging in age, gender, social class, and schooling, that live or have lived in the neighbourhood for at least five years. Each inhabitant participated in an interview using the walking interviews method and the results were determined through a thematic analysis. The results show that these two concepts have significant consequences for the participants: there is a clear preference for the way things were in the past, since they feel that the neighbourhood no longer provides services and spaces adequate for the pre-existing community, decreasing their place dependence to the neighbourhood and consequently their emotional attachment to the place; social bonds within the neighbourhood have suffered alterations due to increase of foreigners and people with greater economic power living in the area, decreasing familiarity and solidarity; lastly, these changes incite feelings of sadness and grief.